Insufficient birth weight risk factors at Tacna Hipolito Unanue Hospital, 2001 – 2010 - Ticona Rendón, Manuel (2013)
Objectives: To determine incidence and risk factors for underweight newborns at Hospital Hipolito Unanue of Tacna. Design: Retrospective, epidemiological case-control study. Setting: Hospital Hipolito Unanue, Tacna, Peru. Population: During years 2 001 to 2 010 we analyzed data of 3 622 live births weighing 2 500 to 2 999 g, from single pregnancies, compared to 24 556 controls weighing 3 000 to 3 999 g. Interventions: We performed bivariate analysis using confidence intervals OR 95%, and multivariate analysis with logistic regression. Perinatal Data System was used. Main outcome measures: Risk factors. Results: The frequency of underweight newborns was 10,77 x 100 live births. Risk factors were illiterate mother (OR=1,98), unmarried (OR=1,41), student (OR=1,4), adolescent (OR=1,38), malnourished (OR=1,84), primiparous (OR=1,35), absence (OR=1,41) or inadequate prenatal care (OR=1,55), hypertensive disease of pregnancy (OR=2,72), premature rupture of membranes (OR=2,09), bleeding in the first (OR=1,37) and second half of pregnancy (OR=1,83) and maternal tuberculosis (OR=5,23). Conclusions: Risk factors associated with low birth weight at Tacna’s Hipolito Unanue Hospital were poor maternal socioeconomic conditions, absent or inadequate prenatal care and maternal pathology.